STUDI AWAL: DAMPAK PENGGUNAAN BAHAN AJAR BERBASIS INKUIRI TERBIMBING TERHADAP KEMANDIRIAN BELAJAR SISWA - Sianipar, Lia Kristina; Gunanto, Yohanes Edi; Izaak, Maya Puspitasari; Rasmi, Dian Pertiwi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This research is a literature review. The purpose of this study is to determine the impact of the use of guided inquiry teaching materials on student learning independence, especially in Physics material. The data in this study are secondary data, namely data obtained from books, journals, articles, and proceedings. Through the review of the information carried out, it was found that guided inquiry teaching materials can encourage students to learn independence in physics material. Teachers are expected to be able to develop guided inquiry teaching materials to train students to learn independence.